Analisis Kandungan Lignin, Sellulosa, dan Hemisellulosa Serat Sabut Kelapa Akibat Perlakuan Alkali - Kondo, Yan; Arsyad, Muhammad (Politeknik Negeri Ujung Pandang, 2018)
The long-term goal of this research is to makecoconut fiber composite as one of the technical material, forbuilding material such as ceiling board or for automotivematerial such as bumper. While the specific target to be achievedin this research is to determine the influence of the concentrationof alkali solution on soaking coconut fiber to the content of lignin,cellulose, and hemicelluloses of coconut fiber. To achieve theobjectives and targets, the method of implementation of thisresearch is divided into 4 (four) steps, namely (1) preparation, (2)immersion, (3) testing, and (4) analysis. Coconut fiber is treatedby soaking coco fiber for 3 hours in sodium hydroxide (alkali)solution with concentrations of 5%, 10%, 15%, 20%, 25%, 30%,35%, 40%, 45%, 50%, and 55%. Once soaked, the coconut fiberis rinsed with aqua, then dried in an oven at 60Â°C for 4 hours.After that, a composition test with hydrolysis method todetermine the content of lignin, cellulose, and hemicelluloses.Each variable will be tested 3 (three) times. The data obtainedwill be analyzed statistically by applying descriptive method,where all data obtained will be presented in table, graphic, orimage form. Based on the tables, graphs, and images will beanalyzed and drawn conclusions. The results to be achieved inthis study is to determine the content of lignin, cellulose, andhemicelluloses coconut fiber due to alkali treatment for 3 hourswith a variable concentration of alkali solution. Based on theresults and discussion it can be concluded that soaking coconutfiber in alkaline solution degrades the content of hemicelluloses,cellulose and lignin.